Pengawasan Internal, Pengawasan Eksternal Dan Kinerja Pemerintah - Widanarto, Agustinus (Jurnal Ilmu Administrasi Negara, 2013)
The research wasmotivated by a problem with the performance of the City of Bandung is not optimal. This study aimsto analyze the influence of internal controls and external controls on the performance of the City ofBandung and developed the concept of controls, in order to obtain the strategy in improving thefunctioning of internal controls and external controls so as to encourage the achievement ofperformance targets Government of Bandung. This study uses explanative. The study populationis all regional work units (SKPD) amounted to 84 SKPD Bandung. Completely investigated as acensus research. Data analysis using Path Analysis, which can explain the influence of direct andindirect effects of independent variables to the dependent variable. The results showed that theinternal controls and external controls together have a strong influence on the performance of theCity of Bandung. Involvement of external factors than internal supervision and monitoring techniqueis the application of external conception of functional theories. Within the framework of middlerange theories in the field of government management, further research is expected to remain focusedon performance evaluation in terms of outcomes.